Survival Outcome of Thoraco‐Laparoscopic McKeown Esophagectomy Versus Endoscopic Submucosal Dissection for Early‐Stage Esophageal Squamous Cell Carcinoma: A Propensity Score‐Matched Analysis - Ping Yuan; Zhenhao Huang; Feichao Bao; Jiajing Li; Lidong Chen; Hongtao Wen; Donglei Liu; Feng Li; Shanfeng Zhang; Yu Qi; Xiangnan Li (Thoracic Cancer)
ABSTRACT Objective To evaluate thoraco‐laparoscopic McKeown esophagectomy (TLME) versus endoscopic submucosal dissection (ESD) for clinical‐T1N0 esophageal squamous cell carcinoma (ESCC) depending on invasion depth. Background Early‐stage ESCC has been widely treated by endoscopic resection. While ESD is safer than esophagectomy perioperatively, its survival benefits for clinical‐T1N0M0 ESCC, especially high‐risk T1b tumors, are unclear. Methods A retrospective study was conducted on clinical‐T1N0 ESCC patients at the First Affiliated Hospital of Zhengzhou University comparing TLME (cT1a, n = 352; cT1b, n = 205) with ESD (cT1a, n = 499; cT1b, n = 62). Overall survival (OS), disease‐specific survival (DSS), relapse‐free survival (RFS), and metastasis‐free survival (MFS) were analyzed depending on invasion depth after propensity score matching to account for selection bias. Results ESD group had better OS (hazard ratio: 0.54, p = 0.029) but worse RFS (hazard ratio: 6.83, p < 0.001) than TLME group in general terms. T1a cancers showed no difference in DSS and MFS between groups. T1b subgroup with ESD had lower DSS (hazard ratio: 5.65, p = 0.036) and MFS (hazard ratio: 3.54, p = 0.069). R1‐resection in ESD group linked to poorer OS (hazard ratio: 5.89, p = 0.006) and DSS (hazard ratio: 3.67, p = 0.006). Conclusion ESD can be safe in the treatment of clinical‐T1aN0 ESCC. However, concerning oncologic curability, TLME should be recommended for patients with clinical‐T1bN0 ESCC in terms of favorable DSS, RFS, and MFS.